Structure of the chorioretinal complex in the rabbit eye after vitrectomy. Report 2. Vitreous cavity irrigation with different temperature solutions for 60 minutes - O.S. Zadorozhnyy; R.E. Nazaretian; V.V. Myrnenko; V.A. Naumenko; E.V. Maltsev; N.V. Pasyechnikova; V.V. Shafranskii (Journal of Ophthalmology, 2018)
Background: It remains poorly understood what should be the temperature of the irrigation solution for intraocular surgery and how long it is reasonable to use irrigation solutions during vitrectomy.